Mid-infrared luminescence of Gd2O3-based nano-glass ceramic with remarkable stability. Issue 22 (15th November 2021) - Li, Jiabo; Chen, Bin; Li, Yinyan; Li, Bingpeng; Huang, Feifei; Lei, Ruoshan; Xu, Shiqing
Abstract: As rare earth ion laser materials, any single kind type matrix can not satisfy the development requirements at the present stage, especially in the application of mid-infrared laser, which needs convenient operation, good physical and chemical properties and luminescent properties. In this study, nanocrystalline units are introduced into the glass structure to integrate their respective advantages and achieve the best balance, so as to obtain nanocrystalline-glass composites (NGC) with both crystal and amorphous properties. The results show that the emission intensity of the composited host is stronger than that of pure amorphous materials; particularly, the intensity of the 2.7 μm emission has been a significant improvement. Moreover, this method not only keeps the size of the nanocrystalline unit, but also affects the energy transfer making use of the nanostructure. Nano-glass ceramics thus might have a significant application potential; they might be used improve the performance of photonic devices and develop nano-integrated multifunctional materials.